The Influence of Mindfulness and Perceived Social Support on Burnout in Teachers with Students with Special Needs - Hanifah Rizki Nurrahmawati; Zahrotun Nihayah (Tazkiya Journal of Psychology, 2025)
This study aims to determine the effect of Mindfulness and Perceived Social Support on all dimensions of Burnout. The sample in this study consisted of 212 teachers with students with special needs. The sampling technique used is non-probability sampling. The scales used in this study are the Maslach Burnout Inventory (MBI), the Mindfulness in Teaching Scale (MTS), and the Multidimensional Scale of Perceived Social Support (MSPSS). Data analysis used in this research is multivariate analysis with the path analysis method, and construct validity is tested using MPLUS 7.11. The results of the analysis show that there is a significant negative effect between intrapersonal mindfulness and perceptions of social support from the family on emotional exhaustion. Interpersonal attention and perceived social support from family and friends influence depersonalization. There is a significant positive effect between perceptions of social support from friends and a lack of achievement, and there is a significant negative effect between perceptions of social support from other people and a lack of achievement. Researchers hope that the implications of the results of this study can be studied and developed in further research.